2020
DOI: 10.1101/2020.06.17.20133918
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher risk of COVID-19 hospitalization for unemployed: an analysis of 1,298,416 health insured individuals in Germany

Abstract: Background: Previous research on infectious disease has revealed that infection risk as well as the severity of diseases is related to income and poverty. In this study we investigate if unemployed persons have a higher risk to become hospitalized with a COVID-19 diagnosis compared with employed persons. Methods: We used routine data on hospitalizations in a study population of 1,298,416persons between the ages 18 and 65 who were enrolled in a German health insurance and who were active on the labour market (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
1
20
0
1
Order By: Relevance
“…Moreover, individuals who were confirmed as COVID‐19‐positive have been reported to suffer from the stigma of COVID‐19 (Bagcchi, 2020; Singh & Subedi, 2020). A recent study reported that the COVID‐19 patients who were admitted to the hospital were at a higher risk of unemployment in Germany (Dragano et al, 2020). Unemployment is known to be a closely related factor to depression according to an epidemiological study (Dooley et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, individuals who were confirmed as COVID‐19‐positive have been reported to suffer from the stigma of COVID‐19 (Bagcchi, 2020; Singh & Subedi, 2020). A recent study reported that the COVID‐19 patients who were admitted to the hospital were at a higher risk of unemployment in Germany (Dragano et al, 2020). Unemployment is known to be a closely related factor to depression according to an epidemiological study (Dooley et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Geography was included as a known predictor of COVID-19 [ 22 ]. Similarly, demographics [ 23 , 24 ], population density [ 25 ], proportion of people aged 65 and older [ 21 ], economic considerations [ 26 ], population health status (comorbidities) [ 27 ], and political considerations [ 28 ] are also known as hypothetical factors that affect infection and death rates, although the reasons for the associations between individual variables and death rates are not fully understood [ 24 ]. We include hospital system characteristics to account for the possibility that lack of resources increase death rates [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Even though Covid-19 is a very recent phenomenon, research points to multiple inequalities in the effects of the pandemic on work-life. Research topics include home office (Fadinger and Schymik 2020), work-careconflicts (Kohlrausch and Zucco 2020), changes in working hours (Eurofound 2020), economic problems (Hövermann 2020;Adams-Prassl et al 2020) and health risks (Dragano et al 2020;ONS 2020). Concerning employees' experience of economic and health risks, it is important to note that previous research has focused on one of the two types of risks; no study has thus far addressed employees' views of both risks concurrently.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies based on public health data, have shown that socio-economic position also impacts corona-related health risks (Bambra et al 2020). In Germany, unemployment is linked to higher risks for a Covid-19 hospitalization (Dragano et al 2020). For England and Wales, the office for national statistics reports considerable occupational inequalities in mortality rates (ONS 2020).…”
Section: Introductionmentioning
confidence: 99%